2022
DOI: 10.1088/1748-605x/ac4e64
|View full text |Cite
|
Sign up to set email alerts
|

Linear-branched poly(β-amino esters)/DNA nano-polyplexes for effective gene transfection and neural stem cell differentiation

Abstract: Controllable regulation of stem cell differentiation is a critical concern in stem cell-based regenerative medicine. In particular, there are still great challenges in controlling the directional differentiation of neural stem cells (NSCs) into neurons. Herein, we developed a novel linear-branched poly(β-amino esters) (S4-TMPTA-BDA-DT, STBD) through a two-step reaction. The synthesized STBD linear branched polymers possess multiple positively charged amine terminus and degradable intermolecular ester bonds, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this special issue, Cao et al developed a novel linear-branched poly (β-amino esters) (called STBD) nanocarrier with multiple positively charged amine terminus and degradable intermolecular ester bonds for efficient gene loading and delivery, and effective gene release and transcription in neural stem cells (NSCs). Thereby, the levels of neuronal differentiation and maturation of NSCs were significantly enhanced after delivering siRNA (shSOX9) expression plasmid into NSCs for silencing the SOX9 gene in NSCs by the STBD nanocarrier [9]. The STBD/deoxyribonucleic acid nano-polyplex may serve as a powerful nonviral approach for gene delivery in NSCs, showing broad application prospects in NSC-based regenerative medicine.…”
Section: Stem Cells Nanobiotechnologiesmentioning
confidence: 99%
“…In this special issue, Cao et al developed a novel linear-branched poly (β-amino esters) (called STBD) nanocarrier with multiple positively charged amine terminus and degradable intermolecular ester bonds for efficient gene loading and delivery, and effective gene release and transcription in neural stem cells (NSCs). Thereby, the levels of neuronal differentiation and maturation of NSCs were significantly enhanced after delivering siRNA (shSOX9) expression plasmid into NSCs for silencing the SOX9 gene in NSCs by the STBD nanocarrier [9]. The STBD/deoxyribonucleic acid nano-polyplex may serve as a powerful nonviral approach for gene delivery in NSCs, showing broad application prospects in NSC-based regenerative medicine.…”
Section: Stem Cells Nanobiotechnologiesmentioning
confidence: 99%
“…A hyperbranched polymer formulation suitable for DNA delivery might not be effective for siRNA delivery, possibly due to differences in their chemical/physical properties and mechanisms of action . Slight structure modifications within pBAEs can significantly affect their efficiency in delivering different nucleic acids. , Therefore, identifying the optimal hyperbranched pBAE polymer formulation for siRNA delivery is crucial. Incorporating optimal monomer combinations and hyperbranching architecture in the pBAE polymer shall achieve efficient gene silencing at a lower polymer/siRNA weight ratio or reduced siRNA dose.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that tuning the polymer structure of pBAEs from linear to a hyperbranched architecture can significantly enhance gene transfection efficiency when delivering plasmid DNA to various cell types, including cancer cells, 37−39 skin cells, 38,40,41 retinal pigment epithelial cells, 42 and stem cells. 43,44 This enhancement may be attributed to hyperbranched pBAEs providing a higher number of tertiary amine groups and terminal end groups, thus promoting better DNA condensation due to their increased cationic charge density and enhanced molecular flexibility. 45 We hypothesize that a hyperbranched architecture could address the limitation of the current pBAE polymer in siRNA delivery by reducing the required amount of polymer carrier or siRNA dose for efficient gene silencing.…”
Section: Introductionmentioning
confidence: 99%